2017
DOI: 10.1016/j.rbmo.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A direct healthcare cost analysis of the cryopreserved versus fresh transfer policy at the blastocyst stage

Abstract: A cost analysis covering direct healthcare costs relating to IVF freeze-all policy was conducted. Normal- and high- responder patients treated with a freeze-all policy (n = 63) compared with fresh transfer IVF (n = 189) matched by age, body mass index, duration and cause of infertility, predictive factors for IVF (number of oocytes used for fertilization) and study period, according to a 1:3 ratio were included. Total costs per patient (€6952 versus €6863) and mean costs per live birth were similar between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…All patients were treated with a GnRH antagonist protocol as previously described [2122]. Briefly, both initial dose of FSH and dose adjustments during treatment were chosen on a case-by-case basis according to patients’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were treated with a GnRH antagonist protocol as previously described [2122]. Briefly, both initial dose of FSH and dose adjustments during treatment were chosen on a case-by-case basis according to patients’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled ovarian stimulation was performed according to the clinical practice and as previously described [ 46 48 ]. Oocyte collection was performed 36 h after triggering of ovulation.…”
Section: Methodsmentioning
confidence: 99%
“…This leads to a lack of regulation or reliable statistics about the real cost to patients. However, Papaleo et al 27 recently compared two embryo transfer strategies aiming to analyse the real costs of each of them in order to choose the best option. From this study it can be observed that the average to achieve a live birth varies between €13,101 and €15,279 according to the transfer policy used.…”
Section: Problematic In Art: Its Impact On Health Cost and Resultsmentioning
confidence: 99%
“…From this study it can be observed that the average to achieve a live birth varies between €13,101 and €15,279 according to the transfer policy used. 27 These numbers show that in spite of the numerous advances in ART, the implantation and pregnancy rates do not increase significantly, and the cost-results ratio is still disproportionate. Dr. Robert Edwards estimated that 85% of embryos transferred in the uterine cavity fail to implant.…”
Section: Problematic In Art: Its Impact On Health Cost and Resultsmentioning
confidence: 99%